Formulating Strategy for Increasing and Stabilizing Third-Party Funds Performance: Case Study on PT Bank ABC Sharia Branch - Shafira Meutia Sanusi; Sudarso Kaderi Wiryono (Politeknik Siber Cerdika Internasional, 2025)
This study aims to formulate a strategy to increase and stabilize the performance of Third-Party Funds (TPF) at PT Bank ABC Sharia Branch (Sharia Branch). TPF plays a critical role in the bank's operational sustainability and competitiveness, but its growth has been inconsistent due to a combination of internal and external factors. To understand the root causes of this instability, the study uses VRIO, PESTLE and SWOT analysis. VRIO (Value, Rarity, Imitability, Organization), PESTLE (Political, Economic, Social, Technological, Legal, and Environmental), and SWOT (Strengths, Weaknesses, Opportunities, and Threats). The VRIO analysis is employed to assess the internal resources and capabilities of Sharia Branch in order to identify elements that can serve as a sustainable competitive advantage. PESTLE analysis offers a broader understanding of the external environment factors such as regulatory support, economic conditions, technological changes, and the growing interest in Islamic financial services. SWOT analysis then integrates these internal and external insights to comprehensively map the bank’s strengths and weaknesses in relation to emerging opportunities and external threats. The findings of the study indicate that the instability of TPF is primarily caused by weak product differentiation, underdeveloped digital services, limited customer education, and insufficient staff training on sharia-compliant products. Moreover, the lack of effective promotions and outreach activities has led to poor customer engagement. Externally, Sharia Branch is constrained by changing economic conditions and the aggressive expansion of competitors who offer more attractive deposit schemes and seamless digital experiences. The bank also faces negative perceptions about the complexity and limited benefits of Islamic banking products, further affecting public interest and trust. This research contributes to the development of a strategic framework that can be applied to other Islamic banks facing similar challenges.